Fabricio Tocco. Latin American Detectives Against Power. Individualism, the State, and Failure in Crime Fiction. Lanham: Lexington Books, 2022. (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2023)
Reseña de Fabricio Tocco. Latin American Detectives Against Power. Individualism, the State, and Failure in Crime Fiction. Lanham: Lexington Books, 2022.